The psychosocial impact of interactive computer use within a vulnerable elderly population: a report on a randomized prospective trial in a home health care setting. - Billipp SH (Public Health Nursing)
Quality of care for vulnerable elderly clients makes it important to consider the psychosocial effects of interactive computer use as a means to communicate for social, functional, and/or health care purposes in a home health care setting. In a 3-month randomized prospective trial, telecommunications terminals were installed in the private residences of computer-illiterate persons, 65-years-of-age and older, providing visiting nurses the opportunity to teach computer use with three different training methods. The control group had similar weekly nurse visits, but no computer terminal use. Pre-posttests using the Rosenberg Self-Esteem Scale and the Geriatric Depression Scale compared change in self-esteem and depression scores of computer-use clients with the scores of the control group clients. Interactive computer use, alone, did not significantly change scores. Compared to the control group, however, there was a significant change toward improved self-esteem and depression when interactive computer use was accompanied with weekly nurse computer training. Weekly training with a significant other, as a substitute for the nurse trainer, significantly improved self-esteem scores but not depression scores. Interactive computer use was not associated with decreased self-esteem or increased depression. Attitude changes and responses to the particular telecommunication service used in this study were mixed, suggesting future research should be based on improved telecommunication systems with access to programs that have greater practical application to the needs of elderly clients.